Trauma, torture, and dissociation : a psychoanalytic view - Alayarian, Aida (Karnac, 2011)
Understanding trauma is central in this book, for both a practical and theoretical challenge from a relational psychoanalytical perspective, with the view that childhood trauma of patient is a dual narration along with the developmental processes as a factor creating resilient qualities. The theoretical material is presented in close conjunction with clinical data in the form of vignettes and case studies to illustrate the key points. Presentation of vignettes and case studies focuses on the multidimensional approach examining the contributions of psychoanalysis, emphasising the act of 'dissoci.